Response of Axonopus catarinensis and Arachis pintoi to shade conditions - Pachas, Anibal Nahuel; Jacobo, Elizabeth Juliana; Goldfarb, Maria Cristina; Lacorte, Santiago María (CIAT, 2021)
In the northeast of Argentina, there are more than 100,000 ha of silvopastoral systems, where trees, forages and live-stock are combined with the goal to diversify income, reduce financial risk, obtain more profit and enhance envi-ronmental benefit (Cubbage et al. 2012). The rapid adoption of these production systems by farmers has gen-erated high demand for information on shade-tolerant forage grass and legume species.